2011
DOI: 10.1007/s11239-011-0577-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of PGE2 in human atherosclerotic plaque on platelet EP3 and EP4 receptor activation and platelet function in whole blood

Abstract: Atherosclerosis has an important inflammatory component. Macrophages accumulating in atherosclerotic arteries produce prostaglandin E(2) (PGE(2)), a main inflammatory mediator. Platelets express inhibitory receptors (EP(2), EP(4)) and a stimulatory receptor (EP(3)) for this prostanoid. Recently, it has been reported in ApoE(-/-) mice that PGE(2) accumulating in inflammatory atherosclerotic lesions might contribute to atherothrombosis after plaque rupture by activating platelet EP(3), and EP(3) blockade has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 31 publications
(48 reference statements)
0
24
0
1
Order By: Relevance
“…Therefore, the authors conclude that PGE 2 , released from damaged vessels and atherothrombotic plaques, promotes thrombus formation via EP3 activation. However, whether human plaques produce biologically relevant amounts of PGE 2 and, therefore, atherothrombotic thrombus formation is increased via EP3 receptor activation has remained unclear: while Tilly et al [22] found bioactive PGE 2 , Schober et al [26] could not show an effect of plaque homogenates on platelet Pselectin expression, GPIIb/IIIa activation or thrombus formation. While in earlier studies a moderate increase in bleeding time was seen in EP3 knockout mice [16,17] , more recent studies in mice as well as in humans demonstrated that the EP3 antagonist prevented EP3-augmented platelet aggregation ex vivo without affecting bleeding time in vivo [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the authors conclude that PGE 2 , released from damaged vessels and atherothrombotic plaques, promotes thrombus formation via EP3 activation. However, whether human plaques produce biologically relevant amounts of PGE 2 and, therefore, atherothrombotic thrombus formation is increased via EP3 receptor activation has remained unclear: while Tilly et al [22] found bioactive PGE 2 , Schober et al [26] could not show an effect of plaque homogenates on platelet Pselectin expression, GPIIb/IIIa activation or thrombus formation. While in earlier studies a moderate increase in bleeding time was seen in EP3 knockout mice [16,17] , more recent studies in mice as well as in humans demonstrated that the EP3 antagonist prevented EP3-augmented platelet aggregation ex vivo without affecting bleeding time in vivo [21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has identified that the effects of PGE 2 on platelet function are mediated mainly through interaction with the EP3 receptor, which promotes platelet function via a G i -linked mechanism, and through interaction with the EP4 receptor, which inhibits platelet function via a G s -linked mechanism [8][9][10][11][12][13][14]. In this study, we have examined the possibility that the action of PGE 2 at EP3 and EP4 receptors can explain the previous observation that this prostaglandin is able to reverse the inhibition of aggregation by agents that stimulate cAMP production via G s , but adds to inhibition provided by agents that raise cAMP through other mechanisms, including the inhibition of cAMP PDE and direct stimulation of adenylate cyclase [15].…”
Section: Discussionmentioning
confidence: 99%
“…Interaction of each agent with its specific receptor leads to activation of adenylate cyclase, via G s , resulting in an increase in cAMP and subsequent inhibition of platelet function. Another naturally occurring prostaglandin, prostaglandin E 2 (PGE 2 ), is able to raise cAMP in a similar manner by interaction with the G s -linked EP4 receptor [9][10][11][12]. However, PGE 2 is unusual in that it also interacts with a second receptor, the G i -linked EP3, to inhibit adenylate cyclase [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…PGE 2 has been found to be the predominant prostanoid from endothelial cells in human microvessels [33] and rabbit coronary microvessels [34], and it likely plays a significant role in angiogenesis [35] and vascular tone [36, 37]. PGE 2 is also present in atherosclerotic plaque [38, 39]. Resident macrophages in atherosclerotic plaque constitutively express COX-1 and make small amounts of PGE 2 at baseline.…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of EP3 via the EP3-specific agonist sulprostone does not directly lead to platelet aggregation, but potentiates aggregation in response to agonists such as ADP and U46,619 in human [38, 56, 62, 72] and murine [73] platelet rich plasma. Additionally, PGE 2 -mediated stimulation of EP3 decreased cAMP, consistent with its primary signaling in platelets being coupled to G i [73].…”
Section: Introductionmentioning
confidence: 99%